The 'spiritual death' of Jesus : a Pentecostal investigation - Atkinson, William, 1961- (Global Pentecostal and Charismatic Studies, 2009)
Winner of the Award of Excellence of the Foundation for Pentecostal Scholarship 2010. The teaching of Kenyon, Hagin and Copeland that Jesus 'died spiritually' (JDS) is important because of the influence of these men, not least on Pentecostalism. JDS originated with Kenyon, and has been taught in the Word-faith movement by Hagin and Copeland, despite much criticism. It incorporates three elements: in this death, Jesus was separated from God; partook of a satanic nature; and was Satan's prey. This theological appraisal takes research far further than previous works, both in method and in scope. It concludes that adoption of JDS by Pentecostalism would be damaging in several respects, and thus draw the latter away from its moorings in traditional Christianity. Pentecostals and others are advised to reject the bulk of this teaching.